1989
DOI: 10.1007/bf01570320
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous mastectomy data: A final statistical analysis of 1500 patients

Abstract: A statistical analysis of 1500 patients who underwent subcutaneous mastectomy is presented. Their data suggest that most patients who were treated by subcutaneous mastectomy had proliferative fibrocystic disease or macrocystic disease, among other high risk factors. The data also suggest that a thoroughly performed subcutaneous mastectomy is an effective means of providing prophylaxis in women who are at high risk for breast cancer. Conclusions were confirmed by many unsolicited comments of patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(40 citation statements)
references
References 13 publications
0
35
1
4
Order By: Relevance
“…At a median follow-up of 14 years, the incidence of new breast cancers was only 1.1%, representing a 91% reduction in risk when compared with female siblings who had not undergone prophylactic mastectomy. Similarly, Ziegler & Kroll (1991), re-analyzing data originally reported by Pennisi & Capozzi (1989), found an incidence of 1.2% in 510 high-risk patients who had undergone prophylactic mastectomy.…”
Section: Prophylactic Mastectomymentioning
confidence: 87%
See 1 more Smart Citation
“…At a median follow-up of 14 years, the incidence of new breast cancers was only 1.1%, representing a 91% reduction in risk when compared with female siblings who had not undergone prophylactic mastectomy. Similarly, Ziegler & Kroll (1991), re-analyzing data originally reported by Pennisi & Capozzi (1989), found an incidence of 1.2% in 510 high-risk patients who had undergone prophylactic mastectomy.…”
Section: Prophylactic Mastectomymentioning
confidence: 87%
“…Subcutaneous mastectomy has been particularly criticized because of the possibility of leaving tissue at the undersurface of the NAC. Although most large-scale studies have reported successful results from subcutaneous www.endocrinology.org 279 mastectomy (Pennisi & Capozzi 1989, Hartmann et al 1999, total mastectomy is considered to be the more definitive procedure.…”
Section: Prophylactic Mastectomymentioning
confidence: 99%
“…olarak sıralanabilir (2). BRCA1 ve 2 analizleri sayesinde yüksek risk taşıdığı tespit edilen hastalarda bilateral profilaktik mastektominin meme kanseri gelişme riskini yaklaşık %90 düşürdüğü (3); yaşam beklentisinin 2,9'dan 5.3 yıla çıktığı birçok çalışma tarafından gösterilmiştir (4 …”
unclassified
“…8,9 The actual risk reduction that is provided by prophylactic mastectomy is presumed to be substantial but cannot be precisely measured due to uncertainty of pre-treatment risk, variable indications, and incomplete follow-up. 10 Even if risk reduction could be quantified, medical, cultural and financial issues make this approach unfeasible in clinical practice for most women.…”
Section: Prophylactic Mastectomymentioning
confidence: 99%